Division of labour among culms in the clonal reed Arundo donax (Poaceae) is underlain by their pre-determined hydraulic structure. (5th August 2020) - Shtein, Ilana; Baruchim, Paz; Lev-Yadun, Simcha
Abstract: Clonal plants present an interesting example of division of labour among their ramets. Here we elaborated on hydraulic structure in respect to the division of labour among ramets in Arundo donax, a perennial clonal reed. Mature clones have three shoot types: (1) large mostly flowering; (2) medium mostly vegetative and (3) small vegetative. The shoots grow from buds initiating in the upper side of underground rhizomes, and the shoot growth is primary with vasculature produced from the procambium. We tested whether the number of vascular strands in a shoot has a fixed developmental programme or follows a flexible developmental pattern, and we found that the number of vascular strands strongly differs between shoot types. Large shoots on average have 560 vascular strands with both the widest vessels and significantly highest hydraulic conductivity. Medium ones and small shoots have 409 and 102 on average, respectively, with narrower vessels and with low conductivity. Thus, the shoot apices have three alternative developmental programmes. Apparently, a clone is built of functionally different modular units that enable Arundo donax to maximize its potential in a heterogeneous environment. Although the smaller culms do not contribute directly to the sexual reproduction of the clone, under stress their safer hydraulic system offers them a better chance of survival.